Plausible Scenarios for Thai Sustainable Energy in 2050: Cloud and Clear - Wangjiraniran, Weerin; Pongthanaisawan, Jakapong; Nakapreecha, Nitida; Nitiphon , Arwut; Suphapong , Suphakanya; Phohphuech , Benjaphat; Thanatsang, Thapana; Vinaisuratern , Prim (International Journal of Energy Economics and Policy, 2022)
This study’s goal is to illustrate future energy scenarios for Thailand in the year 2050: Cloud and Clear scenarios. Cloud depicts a scenario of an economy driven mainly by value-based industrial manufacturing. Security of energy supply is prioritized, with an emphasis on environment concerns and GHG emissions. Energy industry is dominated by incumbent businesses, which play important role in energy transition. Clean energy is gaining more market share, but fossil fuels remain the primary source of energy. Clear reflects the new economy driven by new S-curve businesses. Energy sustainability became first priority for national policy. Diverse options for end-users are available for self-management. New players can be competitor in Thai energy industry. Clean energy became one of the main energy sources. The quantitative results show that owing to the pandemic’s impact, short-term energy demand and GHG emissions decrease dramatically, then rebound and split into two scenarios: uptrend for Cloud and downtrend for Clear. Pathway to sustainable energy is revealed in Clear scenario. Peak energy demand can be reached within 2030. The peak of GHG emissions has already passed and will be approaching to the level of 2DC pathway. Therefore, more actions are required to achieve the ambitious goal of 1.5C.